THE EFFECT OF THE SHORT-TERM LIQUIDITY RATIO ON RETURN ON ASSETS IN FOOD AND BEVERAGE COMPANIES LISTED ON THE IDX (2021–2023) - Rima Dwijayanty; Aryati Lintang Nastiti; Hetti Herawati; Wuri Handayani (PT. Altin Riset Publishing, 2026)
This study aims to examine the effect of the Current Ratio (CR) on Return on Assets (ROA) in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Liquidity, measured by CR, is assumed to influence the firm’s ability to generate profits through the effective utilization of assets. The research applies a quantitative method with a descriptive verification approach. A purposive sampling technique was employed to select 44 companies from a total population of 72. Data were analyzed using simple linear regression with the support of EViews 12. The results reveal that CR has a negative but statistically insignificant effect on ROA, with a significance value of 0.1092, which is greater than the 0.05 threshold. This finding suggests that higher liquidity does not necessarily improve profitability, as excess current assets may hinder efficiency in generating returns. Overall, the study emphasizes the importance of managing liquidity effectively to achieve an optimal balance between solvency and profitability in the food and beverage sector.